Apropriação do conhecimento científico: o sistema patentário a partir do enfoque CTS - Santos, Elis Regina Alves dos (Universidade Federal de São Carlos, 2010)
The field called Science, Technology and Society (STS) is articulated in the late 1960s and early 1970s, trying to understand the scientific-technological phenomenon within the social context. The social appropriation of knowledge becomes a central aspect of concern. Starting from the assumption that the technological training in undergraduate, in current patterns, aligns with an instrumental view of technoscience, this research investigated the understanding of the patent system among students in recent years of courses of exact sciences and technology area, linked to the Center of Exact Sciences and Technology (CEST), from Universidade Federal de São Carlos - UFSCar. More specifically, we attempted to observe how students relate the themes of intellectual property with society, work and academic background. For this we adopted an analytical and descriptive methodology, of qualitative and quantitative character. The original instrument of data collection used was a half-open questionnaire. For the qualitative analysis we used the method of content analysis (CA) applied to the open question of the questionnaire. The results suggest little consolidated knowledge about the patent system and intellectual property as a whole, and the replication of ideas linked to a linear view of scientific-technological development. The patent is seen as instrumental and is strongly linked to the concepts of innovation, competitiveness and development, in addition to commercial and economic values it embodies. Few signs of social concern in relation to the themes of research were found, and it was verified that the university needs to expand its areas of discussion at graduation, introducing, for example, the STS as well as a compulsory subject in undergraduate courses in technology.
Keywords: Desenvolvimento social - ciência, tecnologia e sociedade; Propriedade intelectual; Patentes; Apropriação social do conhecimento; Science, Technology and Society (STS); Social appropriation of knowledge; Intellectual property; Patents; CIENCIAS SOCIAIS APLICADAS